Women's health: a new global agenda. (June 2016) - Norton, Robyn
Robyn Norton is co-founder and Principal Director of The George Institute for Global Health (Australia), a not-for-profit medical research institute that aims to increase the provision of safe, effective and affordable healthcare, especially for disadvantaged populations worldwide. She is Professor of Global Health and James Martin Fellow at the University of Oxford (UK), Professor of Public Health at the University of Sydney (Australia) and Honorary Professor at Peking University (China). Professor Norton is internationally regarded for her research on the causes, prevention and management of injuries and the management of various critical conditions in surgical and intensive care settings. She has had a long-standing commitment to improving women's health, particularly in resource-poor environments.